Determinants of alliance partner choice: Network distance, managerial incentives, and board monitoring - Kang, Ribuga; Zaheer, Akbar (Strategic Management Journal, 2018)
[Research summary: We ask if managerial opportunism is a significant problem in alliance partner choice and examine the role of corporate governance mechanisms in explaining this choice. Using a sample of 313 alliances of U.S. firms from the pharmaceutical and biotechnology industries from 1992 to 2010, we find that managerial incentives lead to managerial preference for relationally risky distant partners over existing and new close partners. Further, board monitoring encourages managers to pursue existing and distant partners over new close ones, choices aligned with shareholder interests. In addition, we find that board monitoring substitutes for managerial incentives in alliance partner choice. We contribute to the literature on alliance partner choice to identify an important, and hitherto, unexplored perspective. Managerial summary: This article examines whether managers and shareholders view alliance-related risks differently, and how the divergent interests between managers and shareholders affect alliance partner choice. We argue that managers' concern about their loss of employment and compensation from alliance failure impedes the choice of relationally risky alliance partners that may increase shareholder value. We also argue that managerial stock ownership and board monitoring mitigate this managerial propensity. Our findings suggest that stock ownership owned by managers and strong board monitoring are effective governance mechanisms to align managers' interests with those of shareholders. Our study offers a novel perspective to understand alliance partner choice by viewing the firm as an entity comprised of fragmented interests.]